Determining the influence of the microstructure and phase composition of glass-metal-ceramic coatings on their basic physical-technical properties - Karasik, Elena; Hordieiev, Yurii (Eastern-European Journal of Enterprise Technologies, 2021)
Given the development of new heat-resistant nickel alloys that operate at temperatures up to 1,250 °C, as well as the introduction of additive technologies for the production of various parts, it is a relevant task to devise new compositions of highly heat-resistant coatings. Determining the influence of the phase composition of glass-metal-ceramic coatings on its basic properties could improve the effectiveness of protecting those parts that operate under extreme conditions. Therefore, it is promising to conduct a study aimed at establishing the relationship between the microstructure and phase composition of glass-metal-ceramic coatings and the main physical-technical characteristics. This study’s results have established that the most high-quality coatings were obtained on the basis of non-crystallizing glass. Such glass is characterized by a temperature coefficient of linear expansion of 92·10-7 degrees-1, a glass transition temperature of 625 °C, and surface tension of 260·10-3 N/m at 850 °C. These properties contribute to the formation of a defect-free coating, providing uniform spreading and high-quality adhesion to the substrate. The resulting optimal coating is characterized by the adhesion strength of 98 %, the thermal resistance (mode 950↔20 °C) of 50 cycles, and the high heat resistance (a weight gain after 100 h in the temperature range of 1,000‒1,050 °C) of 0.03 g/m2·h. Coatings with a minimum amount of glass bonding are distinguished by uniformity and high quality. The optimal ratio of phases "glass:metal-ceramic composition" is 10:90. The structure of the recommended coating is uniform, characterized by the homogeneous distribution of components, the absence of cracks, visible defects, and high quality. The phase composition of the coating after firing is represented by crystals of metallic nickel and silicon, as well as a small amount of residual glass phase.